Pengaruh Kualitas Produk, Fasilitas dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Angkringan Pule - Choiril Seilila Nur Cholifah; Alfina Karismatul Laila; Aldi Nurwana; Mohamad Ajib Markaban Mahiri; Nadia Roosmalita Sari (JMB : Jurnal Manajemen dan Bisnis, 2023)
Consumer satisfaction is able to have a good impact on businesses so that they can develop properly and get maximum profits. This study aims to explain the influence of product quality, facilities, and service quality on customer satisfaction at Angkringan Pule. This type of research is associative using a quantitative approach, to examine how much influence independent variables exert on dependent variables.. The type of data used is primary data obtained from questionnaires with sampling techniques using accidental sampling. In this study, the data were analyzed using data quality tests (validity test, reliability test), classical assumption test (normality test, multicholinearity test, heteroskedasticity test), multiple linear regression test, hypothesis test (F test and t test), coefficient of determination(R2). The results of this study show that product quality, facilities, and service quality have a positive and significant effect on consumer satisfaction both partially and simultaneously.